Molecular Mechanisms Underlying the Divergent Roles of SPARC in Human Carcinogenesis - Nagaraju, Ganji Purnachandra; Dontula, Ranadheer; Bassel, El-Rayes F.; Lakka, Sajani S (Carcinogenesis (New York), 2014)
Communication between the cell and its surrounding environment, consisting of proteinaceous (non-living material) and extracellular matrix (ECM), is important for bio-physiological and chemical signaling. This signaling results in a range of cellular activities, including cell division, adhesion, differentiation, invasion, migration, and angiogenesis. The ECM non-structural secretory glycoprotein called “secreted protein, acidic and rich in cysteine (SPARC), plays a significant role in altering cancer cell activity and the tumor's microenvironment (TME). However, the role of SPARC in cancer research has been the subject of controversy. This review mainly focuses on recent advances in understanding the contradictory nature of SPARC in relation to ECM assembly, cancer cell proliferation, adhesion, migration, apoptosis and tumor growth.